2007
DOI: 10.1177/1090198106296770
|View full text |Cite
|
Sign up to set email alerts
|

What Does the Public Know About Preventing Cancer? Results From the Health Information National Trends Survey (HINTS)

Abstract: This study provides information about the public's familiarity with cancer prevention strategies and examines the association between this familiarity and actual prevention behavior. Data from interviews with 5,589 adults included in the 2003 Health Information National Trends Survey (HINTS) were analyzed. Most respondents were able to cite one or two strategies for reducing the chances of cancer. On average, the fewest number of strategies were cited by Hispanics, respondents aged 65 years or older, and those… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
67
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(116 citation statements)
references
References 24 publications
8
67
1
Order By: Relevance
“…This is consistent with findings from a previous survey conducted in the US [13]. A survey in Great Britain [25] also suggested low awareness of the link between overweight and cancers.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…This is consistent with findings from a previous survey conducted in the US [13]. A survey in Great Britain [25] also suggested low awareness of the link between overweight and cancers.…”
Section: Discussionsupporting
confidence: 92%
“…A survey of US adults revealed that avoiding tobacco and eating a healthy diet were the most commonly cited strategies for preventing cancer; however, less recognition was given to other known important risk factors such as being physically inactive, overweight, or consuming large amounts of alcohol [13].…”
Section: Introductionmentioning
confidence: 98%
“…Obesity in the US continues to escalate and awareness of overweight and obesity as a CRC risk remains low in the general population[48] and among those with high BMI[49]. Low perceived risk for CRC in concert with less worry about CRC is associated with intentions not to screen[5051].…”
Section: Discussionmentioning
confidence: 99%
“…In terms of cancer prevention KAB of the general public, systematic longitudinal research with the launch of the National Cancer Institute Health Information National Trends Survey (HINTS) in the USA has indicated high levels of knowledge for tobacco reduction and improved nutrition, but less familiarity with decreasing alcohol use, physical activity, maintaining a healthy body weight, and especially participation in screening initiatives [39,40]. A recent scoping review of 200 studies on public attitudes toward government intervention for cancer prevention across the four risk factors found overall high support for government intervention for tobacco control, healthy eating, and physical activity, with more variable levels of support for alcohol control [41].…”
Section: Introductionmentioning
confidence: 99%